Cooperative Multifunctional Catalysts for Nitrone Synthesis: Platinum Nanoclusters in Amine‐Functionalized Metal–Organic Frameworks. (22nd November 2017) - Li, Xinle; Zhang, Biying; Tang, Linlin; Goh, Tian Wei; Qi, Shuyan; Volkov, Alexander; Pei, Yuchen; Qi, Zhiyuan; Tsung, Chia‐Kuang; Stanley, Levi; Huang, Wenyu
Abstract: Nitrones are key intermediates in organic synthesis and the pharmaceutical industry. The heterogeneous synthesis of nitrones with multifunctional catalysts is extremely attractive but rarely explored. Herein, we report ultrasmall platinum nanoclusters (PtNCs) encapsulated in amine‐functionalized Zr metal–organic framework (MOF), UiO‐66‐NH2 (Pt@UiO‐66‐NH2 ) as a multifunctional catalyst in the one‐pot tandem synthesis of nitrones. By virtue of the cooperative interplay among the selective hydrogenation activity provided by the ultrasmall PtNCs and Lewis acidity/basicity/nanoconfinement endowed by UiO‐66‐NH2, Pt@UiO‐66‐NH2 exhibits remarkable activity and selectivity, in comparison to Pt/carbon, Pt@UiO‐66, and Pd@UiO‐66‐NH2 . Pt@UiO‐66‐NH2 also outperforms Pt nanoparticles supported on the external surface of the same MOF (Pt/UiO‐66‐NH2 ). To our knowledge, this work demonstrates the first examples of one‐pot synthesis of nitrones using recyclable multifunctional heterogeneous catalysts.